(untitled) (Third Sector Social Economic Review, 2026)
Professional accountants play a crucial role in ensuring that businesses record their commercial activities in compliance with legislation and generally accepted accounting principles and standards. They are responsible for maintaining accounting records, preparing financial statements, filing tax returns, conducting reporting, auditing accounts, and presenting this information to relevant stakeholders. This study examines the effect of sectoral economic growth in Turkey on the employment of professional accountants at the provincial level, using panel data analysis. The panel dataset, constructed from economic activity and accounting employment data for 71 provinces over the period 2009–2023, provided evidence of cross-sectional dependence and slope heterogeneity. Accordingly, a second-generation estimation method, the Augmented Mean Group (AMG), was employed. The results indicate that the effect of economic growth on accounting employment differs across sectors. Specifically, growth in the finance and insurance sectors, as well as in public administration, education, health, and social services, exerts a significant and positive influence on employment. In contrast, growth in agriculture, industry, manufacturing, and general services did not show a statistically significant effect on accounting employment. These findings suggest that economic growth in Turkey does not consistently translate into employment opportunities, highlighting the prevalence of a non-employment-generating growth phenomenon.